2002
DOI: 10.1016/s0304-3959(01)00489-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of quantitative trait loci for chemical/inflammatory nociception in mice

Abstract: Sensitivity to pain is widely variable, and much of this variability is genetic in origin. The specific genes responsible have begun to be identified, but only for thermal nociception. In order to facilitate the identification of polymorphic, pain-related genes with more clinical relevance, we performed quantitative trait locus (QTL) mapping studies of the most common assay of inflammatory nociception, the formalin test. QTL mapping is a technique that exploits naturally occurring variability among inbred stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…3A). By interbreeding mice of this strain with those of a less sensitive strain, one can create a genetically segregating population that can be used to map the chromosomal locations of these genes by linkage (e.g., Mogil et al, 1997;Wilson et al, 2002). The C57BL/6 strain as a progenitor is of particular use in this capacity, since recombinant inbred lines descendent from DBA/2 and C57BL/6 hybrids are available, and both genotypes have been fully sequenced.…”
Section: Discussionmentioning
confidence: 99%
“…3A). By interbreeding mice of this strain with those of a less sensitive strain, one can create a genetically segregating population that can be used to map the chromosomal locations of these genes by linkage (e.g., Mogil et al, 1997;Wilson et al, 2002). The C57BL/6 strain as a progenitor is of particular use in this capacity, since recombinant inbred lines descendent from DBA/2 and C57BL/6 hybrids are available, and both genotypes have been fully sequenced.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic linkage mapping, a technique commonly used to map regions of the genome associated with a phenotype of interest, has facilitated the identification of at least 14 pain-related quantitative trait loci (QTL) in the laboratory mouse to date (Devor et al 2005, 2007; Furuse et al 2003; Honda and Takano 2009; LaCroix-Fralish et al 2009; Mogil et al 1997, 2005b, 2006; Nair et al 2011; Nissenbaum et al 2010; Seltzer et al 2001; Wilson et al 2002). Most current mapping populations are produced using traditional two-strain breeding schemes, resulting in QTL spanning an average of ~30 Mbp and containing hundreds of potential candidate genes.…”
Section: Introductionmentioning
confidence: 99%
“…These QTLs are in the same region as Nociq2 , the QTL previously linked to murine sensitivity in the early and late phases of the intraplantar formalin test of inflammatory nociception [52]. Although the current results may appear to resolve Nociq2 into two loci as previously suspected but not concluded upon [52], multiple QTL modeling performed in the current study does not permit the conclusion that there are two independent loci. The loci cannot be quantitatively distinguished, due to linkage between the loci in the BXD RI strains, but it also cannot be concluded that the two loci are in fact a single locus.…”
Section: Discussionmentioning
confidence: 53%
“…Rodent studies have demonstrated that genetic background significantly affects sensitivity to a number of inflammatory insults [23,52]. Although many genes have been implicated in the modulation of inflammatory nociception using knockout mouse and other techniques [20], the genes responsible for heritable individual differences are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation